2014
DOI: 10.1165/rcmb.2013-0357oc
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Airway Epithelial Antiviral Immunity by Fungal Exposure

Abstract: Multiple pathogens, such as bacteria, fungi, and viruses, have been frequently found in asthmatic airways and are associated with the pathogenesis and exacerbation of asthma. Among these pathogens, Alternaria alternata (Alt), a universally present fungus, and human rhinovirus have been extensively studied. However, their interactions have not been investigated. In the present study, we tested the effect of Alt exposure on virus-induced airway epithelial immunity using live virus and a synthetic viral mimicker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
4
3
1
Order By: Relevance
“…3A, B, and C), but activation of NF-κB was not affected. This observation is consistent with previous reports (28,29). Recently, we have reported a rapid dephosphorylation of IFN-β-induced phospho-STAT1 triggered by AF extract and have confirmed this in the present study (Supplemental Fig.…”
Section: Suppression Of Poly I:c-induced Cxcl10 By Af Extract Was Medsupporting
confidence: 94%
See 1 more Smart Citation
“…3A, B, and C), but activation of NF-κB was not affected. This observation is consistent with previous reports (28,29). Recently, we have reported a rapid dephosphorylation of IFN-β-induced phospho-STAT1 triggered by AF extract and have confirmed this in the present study (Supplemental Fig.…”
Section: Suppression Of Poly I:c-induced Cxcl10 By Af Extract Was Medsupporting
confidence: 94%
“…Previous studies by our laboratory and others have shown that extracts of Aspergillus fumigatus suppress Page 13 of 44 activation of epithelial cells by either IFN or by the TLR3 agonist poly I:C (6,18,28,29). In the present study, we show that AF extract also suppressed the HRV16-induced innate immune response in fully differentiated NHBE cells using an air liquid interface culture system (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…The authors found that fungal proteases were involved in the induction of proinflamatory cytokines and were also responsible for the enhancement of virus-induced cytokine production by Alternaria. These authors also found that Alternaria suppresses virus-induced IFN-b production by a protease-independent mechanism (35). Our studies demonstrate an AF suppression of the response to IFN-b and may help to explain some of the findings of Zhu and colleagues (35).…”
Section: Discussionsupporting
confidence: 70%
“…These authors also found that Alternaria suppresses virus-induced IFN-b production by a protease-independent mechanism (35). Our studies demonstrate an AF suppression of the response to IFN-b and may help to explain some of the findings of Zhu and colleagues (35).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation